(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The nasal obstruction is one of the causes that affect the middle ear function, but the physiological mechanism of this effect is not well understood. This study aims at 1st; evaluation of the middle ear function among adults with chronic nasal obstruction due to sinonasal pathology using tympanometry, and 2nd, at comparison between the anatomical and mucosal inflammatory causes of nasal obstruction and its impact on the middle ear function. Patients and Method: A prospective case study of (310) adult patients with chronic nasal obstruction were subjected to tympanometry for study of middle ear pressure in the private ENT clinic for a period of two years in the Salah Al-Deen governorate. Results: this study found that (13%) of adults with chronic nasal obstruction had abnormal tympanogram (type B or C), (17.2%) was due to mucosal inflammation and (7%) due to anatomical and structural cause. Commonly one ear affected (unilateral) was (67.5%). Myringotomy and aspiration of middle ear found that (64%) had OME and VT was inserted. Conclusion: The study statistically proved that adults with chronic nasal obstruction due to mucosal inflammation differs from others due to anatomical and structural causes in the followings; 1.The incidence of abnormal tympanogram (type B and C) is more. 2.The type B (OME) was more than type C (Eustachian tube dysfunction). 3.In the treatment ,it was found that the need to VT insertion was more.